Academic Writing for Africa - Schmied, Josef J.; Hofmann, Matthias; Esimaje, Alexandra (REAL studies., 2018)
The present volume draws on the experience of the Workshop held in Benin City, Nigeria in May 2018, where doctoral students and experienced mentors met to work on their journal articles from a simple abstract or a first draft to a concrete publication proposal. Since research articles are the most important academic texts in academic careers today, young African scholars must practice to choose current topics, to use appropriate methodologies and argumentation structures, to draw tentative conclusions, and to be aware of limitations and further research necessary in their field. Mentors can advise them to apply proper statistical procedures, to edit their texts carefully and to submit them in acceptable format to appropriate journals. The contributions can also serve as a general model for open and critical international and intercultural academic discourse on publishing research articles in international journals.